Mitophagy-Mediated mtDNA Release Aggravates Stretching-Induced Inflammation and Lung Epithelial Cell Injury via the TLR9/MyD88/NF-κB Pathway - Jing, Ren; Hu, Zhao-Kun; Lin, Fei; He, Sheng; Zhang, Sui-Sui; Ge, Wan-Yun; Dai, Hui-jun; Du, Xue-Ke; Lin, Jin-Yuan; Pan, Ling-Hui (Frontiers in Cell and Developmental Biology, 2020)
Background In animal models of ventilation-induced lung injury, mitophagy triggers mitochondria damage and the release of mitochondrial (mt) DNA, which activates inflammation. However, the mechanism of this process is unclear. Methods A model of cyclic stretching (CS)-induced lung epithelial cell injury was established. The genetic intervention of phosphatase and tensin homolog-induced kinase 1 (PINK1) expression via lentivirus transfection was used to identify the relationship between PINK1-mediated mitophagy and mtDNA release in stretching-induced inflammatory response and injury. Pharmacological inhabitation of Toll-like receptor 9 (TLR9) and myeloid differentiation factor 88 (MyD88) expression was performed via their related inhibitors, while pre-treatment of exogenous mtDNA was used to verify the role of mtDNA in stretching-induced inflammatory response and injury. Results Using a cell culture model of CS, we found that knocking down PINK1 in lung epithelial cells reduced mitophagy activation and mtDNA release, leading to milder inflammatory response and injury; conversely, up-regulating PINK1 exacerbated stretching-induced inflammation and injury, and similar effects were observed by upregulating TLR9 to induce expression of MyD88 and nuclear factor-κB (NF-κB)/p65. Down-regulating MyD88 protected lung epithelial cells from stretching injury and decreased NF-κB/p65 expression. Conclusion These findings suggest that PINK1-dependent mitophagy and associated TLR9 activation is indeed a major factor in stretch-induced cell injury via a mechanism in which released mtDNA activates TLR9 and thereby the MyD88/NF-κB pathway. Inhibiting this process may be a therapeutic approach to prevent inflammation and cell injury in patients on mechanical ventilation.